2009
DOI: 10.3174/ajnr.a1544
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Atrophy in Essential Tremor Using an Automated Segmentation Method

Abstract: BACKGROUND AND PURPOSE:Essential tremor (ET) is a slowly progressive disorder characterized by postural and kinetic tremors most commonly affecting the forearms and hands. Several lines of evidence from physiologic and neuroimaging studies point toward a major role of the cerebellum in this disease. Recently, voxel-based morphometry (VBM) has been proposed to quantify cerebellar atrophy in ET. However, VBM was not originally designed to study subcortical structures, and the complicated anatomy of the cerebellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 14 publications
5
111
2
4
Order By: Relevance
“…6,8,9 VBM is a morphologic technique that performs a statistical mapping of differences in brain morphology voxel-by-voxel, which produces gray matter "attenuation" or "concentration" measures or volume differences between the 2 groups; alternatively, manual/automatic volumetry is a quantitative measurement of specific brain regions in individual brains. 9,10 Quantitative morphologic assessment of individual brain structures is often based on volumetric measurements. Volume changes are intuitive features because they might explain atrophy or dilation due to illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,9 VBM is a morphologic technique that performs a statistical mapping of differences in brain morphology voxel-by-voxel, which produces gray matter "attenuation" or "concentration" measures or volume differences between the 2 groups; alternatively, manual/automatic volumetry is a quantitative measurement of specific brain regions in individual brains. 9,10 Quantitative morphologic assessment of individual brain structures is often based on volumetric measurements. Volume changes are intuitive features because they might explain atrophy or dilation due to illness.…”
Section: Discussionmentioning
confidence: 99%
“…This approach provides advantages similar to those of manual ROI drawing, 13,14 without the potential for rater bias, offering an anatomically accurate rendering of regional volumes. 10 Total intracranial volume was calculated and was used to correct the regional brain volume measurements. 15 Normalized hippocampal values were calculated as follows: [raw hippocampal volume/total intracranial volume] ϫ 1000.…”
Section: Automated Hippocampal Volumetrymentioning
confidence: 99%
“…Several MR imaging studies, published in the past decade, sought to detect ET-specific morphologic abnormalities. Most studies highlighted atrophic changes in different lobules of the cerebellum 32,33 (but also in other brain regions 34,35 ).…”
Section: The Need For Neuroimaging Markers As a Diagnostic Tool For Etmentioning
confidence: 99%
“…Whole-brain analysis, on the other hand, allows exploration of widespread networks but may not be specific enough, with the risk of ignoring smaller regions and nuclei. 41 The data that make up all of the neuroimaging descriptions of ET were acquired at different magnet field strengths (most at 1.5T 32,33,36,40,46 and 3T 34,35,41,42,44 ). Accordingly, contrast and resolution, the parameters that, for the most part, guide the interpretation and analysis of the images, cannot be assumed constant.…”
Section: Potential Bias In Et Neuroimaging Studiesmentioning
confidence: 99%
“…Much of the literature supports that ET is a disorder of cerebellar dysregulation, including the presence of intention tremor [Leegwater- Kim et al 2006;Louis et al 2009b], gait ataxia [Singer et al 1994;Stolze et al 2001], oculomotor abnormalities [Helmchen et al 2003] and problems with dysrhythmia and motor learning [Trillenberg et al 2006;Avanzino et al 2009;Bares et al 2010;Farkas et al 2006;Shill et al 2009;Kronenbuerger et al 2007]. In addition, postmortem studies in ET have indicated the presence of a variety of structural and degenerative changes in the cerebellum, including increased number of Purkinje cell axonal swellings ('torpedoes') [Louis et al 2007b;Axelrad et al 2008], increased number of displaced or heterotopic Purkinje cells [Kuo et al 2011], reduction in number of Purkinje cells in some studies [Axelrad et al 2008] [Bucher et al 1997], positron emission tomography [Jenkins et al 1993;Wills et al 1994;Colebatch et al 1990], 1 H magnetic resonance spectroscopic imaging [Louis et al 2002;Pagan et al 2003], diffusion tensor imaging [Shin et al 2008;Klein et al 2011;Nicoletti et al 2010], voxelbased morphometry [Benito-Leon et al 2009;Quattrone et al 2008] and studies using other automated volumetric methods [Cerasa et al 2009] which demonstrate the presence of functional, metabolic and structural abnormalities in the cerebellum of ET patients.…”
Section: Current Literature On the Relationships Between Et And Cognimentioning
confidence: 99%